2005
DOI: 10.1073/pnas.0505156102
|View full text |Cite
|
Sign up to set email alerts
|

Three genomes differentially contribute to the biosynthesis of benzoxazinones in hexaploid wheat

Abstract: Hexaploid wheat (Triticum aestivum) accumulates benzoxazinones (Bxs) as defensive compounds. Previously, we found that five Bx biosynthetic genes, TaBx1-TaBx5, are located on each of the three genomes (A, B, and D) of hexaploid wheat. In this study, we isolated three homoeologous cDNAs of each TaBx gene to estimate the contribution of individual homoeologous TaBx genes to the biosynthesis of Bxs in hexaploid wheat. We analyzed their transcript levels by homoeolog-or genome-specific quantitative RT-PCR and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
144
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(162 citation statements)
references
References 47 publications
14
144
0
3
Order By: Relevance
“…Previous studies showed that homeologs of the same metabolic gene could also contribute differently to metabolite biosynthesis and accumulation in hexaploid wheat (Nomura et al, 2005). In several instances, significant differences in HYD1-or HYD2-specific homeolog expression among different genomes (A, B, and D genomes) were observed (Fig.…”
Section: Tissue-and Grain Developmental Stage-specific Expression Ofmentioning
confidence: 84%
“…Previous studies showed that homeologs of the same metabolic gene could also contribute differently to metabolite biosynthesis and accumulation in hexaploid wheat (Nomura et al, 2005). In several instances, significant differences in HYD1-or HYD2-specific homeolog expression among different genomes (A, B, and D genomes) were observed (Fig.…”
Section: Tissue-and Grain Developmental Stage-specific Expression Ofmentioning
confidence: 84%
“…In Ha, a locus that influences grain hardness, a large genomic deletion has occurred independently in the A and B genomes, and only the Ha locus genes present on the D genome (Pina, Pinb, and Gsp-1) are functional (Chantret et al, 2005). In Ta Bx, a gene responsible for biosynthesis of benzoxazinones (Bx), expression analysis and the determination of the proteins' catalytic properties revealed that a homoeolog from the B genome is generally the largest contributor to Bx biosynthesis (Nomura et al, 2005). These studies indicated that expression of homoeologous genes is regulated by genetic or epigenetic mechanisms.…”
Section: The Three Wlhs1 Homoeologs Show a Differential Contributionmentioning
confidence: 99%
“…They are especially relevant during infection by necrotrophic pathogens, which rely on tissue injury and host cell death for effective infection [7]. Benzoxazinoids (BXs) are the predominant phytoanticipin in the major Poaceae crop plants, maize and wheat, but are absent from oat, rice and sorghum [10][11][12][13]. Interestingly, unlike Poaceae crop plants, where BXs are limited to seedlings or young plants, dicot plants accumulate BXs during all developmental stages in both above and below-ground parts [14].…”
Section: The Role Of Secondary Metabolites In Defence In Cereal Cropsmentioning
confidence: 99%
“…Instead, this crop relies heavily on phytoanticipins such as BXs for protection against infection [12]. The principal BX in maize and wheat is 2,4-dihydroxy-7-methoxy-1,4-benzoxazin-3-one (DIMBOA) [13] whereas dicot plants only produce the DIMBOA precursor, DIBOA, and its glucoside DIBOA-glc [6].…”
Section: Phytoanticipins Are Stimulated By Jasmonic Acid In Wheat Andmentioning
confidence: 99%
See 1 more Smart Citation